Distribution of oral ulceration cases in Oral Medicine Integrated Installation of Universitas Padjadjaran Dental Hospital - Zakiawati, Dewi; Nur'aeny, Nanan; Setiadhi, Riani (Universitas Padjadjaran, 2020)
Introduction: Oral ulceration defines as discontinuity of the oral mucosa caused by the damage of both epithelium and lamina propria. Among other types of lesions, ulceration is the most commonly found lesion in the oral mucosa, especially in the outpatient unit. Oral Medicine Integrated Installation (OMII) Department in Universitas Padjadjaran Dental Hospital serves as the centre of oral health and education services, particularly in handling outpatient oral medicine cases. This research was the first study done in the Department which aimed to observe the distribution of oral ulceration in OMII Department university Dental Hospital. The data is essential in studying the epidemiology of the diseases. Methods: The research was a descriptive study using the patient’s medical data between 2010 and 2012. The data were recorded with Microsoft® Excel, then analysed and presented in the table and diagram using GraphPad Prism® Results: During the study, the distribution of oral ulceration cases found in OMII Department was 664 which comprises of traumatic ulcers, recurrent aphthous stomatitis, angular cheilitis, herpes simplex, herpes labialis, and herpes zoster. Additionally, more than 50% of the total case was recurrent aphthous stomatitis, with a precise number of 364. Conclusion: It can be concluded that the OMII Department in university Dental Hospital had been managing various oral ulceration cases, with the most abundant cases being recurrent aphthous stomatitis.